Integration of Child Developmental Psychology and Character Education in School Culture: Challenges of Indonesian Education in the Era of Digitalization - Syaifudin Zuhri Syaifudin; Ari Susetiyo (MEDIA DAN STRATEGI PEMBELAJARAN, 2026)
The era of digitalization has significantly transformed the landscape of education in Indonesia, not only in terms of learning technology but also in the psychological dynamics and character formation of children. This article aims to analyze the integration of child developmental psychology and character education within school culture, as well as to identify the challenges of its implementation in Indonesia. This study employs a systematic literature review approach of scientific publications from 2020–2025 that are relevant to the themes of character education, school culture, and developmental psychology in the digital era. The findings indicate that digitalization influences children’s cognitive, socio-emotional, and moral development. Therefore, character education approaches must be grounded in an understanding of psychological developmental stages. School culture serves as the primary medium for internalizing values through habituation, role modeling, and the hidden curriculum. However, the integration of these elements faces psychological, cultural, and structural challenges. This article proposes a three-pillar integrative model psychological, cultural, and digital ethics as a conceptual framework for strengthening character education in Indonesia